Analysis of the Intrinsic Uncertainties in the Laser-Driven Iron Hugoniot Experiment Based on the Measurement of Velocities - 章欢 段晓溪 张琛 刘浩 张惠鸽 薛全喜 叶青 王哲斌 蒋刚 (Chinese physics letters, 2016)
One of the most challenging tasks in the laser-driven Hugoniot experiment is how to increase the reproducibility and precision of the experimental data to meet the stringent requirement in validating equation of state models. In such cases, the contribution of intrinsic uncertainty becomes important and cannot be ignored. A detailed analysis of the intrinsic uncertainty of the aluminum-iron impedance-match experiment based on the measurement of velocities is presented. The influence of mirror-reflection approximation on the shocked pressure of Fe and intrinsic uncertainties from the equation of state uncertainty of standard material are quantified, Furthermore, the comparison of intrinsic uncertainties of four different experimental approaches is presented. It is shown that, compared with other approaches including the most widely used approach which relies on the measurements of the shock velocities of AI and Fe, the approach which relies on the measurement of the particle velocity of Al and the shock velocity of Fe has the smallest intrinsic uncertainty, which would promote such work to significantly improve the diagnostics precision in such an approach.